156k views
0 votes
Calcula el cuadrado de cada binomio: A. (9 + 4m)^2

B. (X^10 - 5y^2)^2
C. (2x - 3z)^2
D. (4m^5 + 5n^3)^2
E. (3/6w - 1/2y)^2
F. (X10 - 5y2)2​

User Wig
by
4.9k points

1 Answer

4 votes

Answer:

Part A)
(9+4m)^(2)=81+72m+16m^(2)

Part B)
(x^(10)-5y^(2))^(2)=x^(20)-10x^(10)y^(2)+25y^(4)

Part C)
(2x-3z)^(2)=4x^(2)-12xz+9z^(2)

Part D)
(4m^(5)+5n^(3))^(2)=16m^(10)+40m^(5)n^(3)+25n^(6)

Part E)
((3)/(6)w-(1)/(2)y)^(2)=(9)/(36)w^(2)-(3)/(6)wy+(1)/(4)y^(2)

Part F)
(x^(10)-5y^(2))^(2)=x^(20)-10x^(10)y^(2)+25y^(4)

Explanation:

The question in English is

Calculate the square of each binomial

we know that

The square of a binomial is always a trinomial

so


(a+b)^(2)=a^(2)+2ab+b^(2)

and


(a-b)^(2)=a^(2)-2ab+b^(2)

Part A) we have


(9+4m)^(2)

Applying the formula


(9+4m)^(2)=(9)^(2)+2(9)(4m)+(4m)^(2)


(9+4m)^(2)=81+72m+16m^(2)

Part B) we have


(x^(10)-5y^(2))^(2)

Applying the formula


(x^(10)-5y^(2))^(2)=(x^(10))^(2)-2(x^(10))(5y^(2))+(5y^(2))^(2)


(x^(10)-5y^(2))^(2)=x^(20)-10x^(10)y^(2)+25y^(4)

Part C) we have


(2x-3z)^(2)

Applying the formula


(2x-3z)^(2)=(2x)^(2)-2(2x)(3z)+(3z)^(2)


(2x-3z)^(2)=4x^(2)-12xz+9z^(2)

Part D) we have


(4m^(5)+5n^(3))^(2)

Applying the formula


(4m^(5)+5n^(3))^(2)=(4m^(5))^(2)+2(4m^(5))(5n^(3))+(5n^(3))^(2)


(4m^(5)+5n^(3))^(2)=16m^(10)+40m^(5)n^(3)+25n^(6)

Part E) we have


((3)/(6)w-(1)/(2)y)^(2)

Applying the formula


((3)/(6)w-(1)/(2)y)^(2)=((3)/(6)w)^(2)-2((3)/(6)w)((1)/(2)y)+((1)/(2)y)^(2)


((3)/(6)w-(1)/(2)y)^(2)=(9)/(36)w^(2)-(3)/(6)wy+(1)/(4)y^(2)

Part F) we have


(x^(10)-5y^(2))^(2)

Applying the formula


(x^(10)-5y^(2))^(2)=(x^(10))^(2)-2(x^(10))(5y^(2))+(5y^(2))^(2)


(x^(10)-5y^(2))^(2)=x^(20)-10x^(10)y^(2)+25y^(4)

Note the problem F is the same problem B

User Pranjal Diwedi
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.